The bodies keep coming : dispatches from a Black trauma surgeon on racism, violence, and how we heal - Williams, Brian H. (Surgeon) (Broadleaf Books, 2023)
"Dr. Brian H. Williams has seen it all, from gunshot wounds to traumatic brain injuries. In The Bodies Keep Coming, Williams ushers us into the trauma bay, where the wounds of a national emergency amass. Black bodies will continue to be wracked by violence, racism, and healthcare inequities until we enact changes of policy and law"-- Provided by publisher.
Keywords: Williams, Brian H. -- (Surgeon); African American surgeons -- Biography.; Surgeons -- United States -- Biography.; Gunshot wounds -- Surgery -- United States.; Discrimination in medical care -- United States.; Racism -- United States.; Gunshot wounds.; Surgeons; Racism; Wounds, Gunshot; Chirurgiens noirs américains -- Biographies.; Chirurgiens -- États-Unis -- Biographies.; Lésions et blessures par armes à feu -- Chirurgie -- États-Unis.; Discrimination dans les soins médicaux -- États-Unis.; Racisme -- États-Unis.; Lésions et blessures par armes à feu.; BIOGRAPHY & AUTOBIOGRAPHY / Medical (incl. Patients); African American surgeons; Discrimination in medical care; United States; Biographies